Comparison of the Egg Characteristics of Different Sudanese indigenous Chicken Types - Mohammed, M.D.; Abdalsalam, Y.I.; Kheir, A.M.; Jin-yu, W.; Hussein, M.H. (Science Alert, 2005)
Three local types of Sudanese indigenous fowls, large Baladi (LB), Bare-neck (BN) and Betwil (BT) were studied for detection of maturity live weight and egg characteristics. The (BN) average live weight (1547.2±274.5 gm) was heavier than either (LB) (1494.4±349.8 gm) or (BT) (1198.3±257.5 gm), The Betwil average live weight is significantly (P